(untitled) (ResearchJet Journal of Analysis and Inventions, 2022)
This study aimed to set standard levels of the level of physical efficiency of the preparatory study stage of ages (16-17) years of age. Obesity and health risks due to international deficiency in order to identify the researcher, the descriptive curriculum, as the total of the sample (1110) was a student from various schools in northern Basra preparatory) by (370) students for each study stage. It also included some measurements for (length, weight, vertical jump .